HUBUNGAN GANGGUAN MENSTRUASI DENGAN INDEKS MASA TUBUH (IMT) PADA SISWI SMP KARYA IBU PALEMBANG TAHUN 2019 - Yona Sari; Tiara Fatrin; Aryanti Aryanti; Mirta i Andan (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
Melnstrulation is a blelelding from thel ultelruls that occulrs pelriodically and cyclic. Caulsels of melnstrulal disordelr dulel to biologic and patalogic disordelr. Othelrs factors affelcting melnstrulal disordelr incluldel strelss, nultrition statuls, agel, and physical activity. Thelrel is a hormonal imbalancel, an immatulrel relprodulctivel delvicel and a p psychic activity. Thelrel is a still morel pronel to occulr in youlng womeln so that melnstrulal disordelr arel morel commonly elxpelrielnceld (Kulsmiran, 2014). Thel pulrposel of thel relselarch was to know thel correllation of melnstrulation disordelr with thel (BMI) on girl stuldelnts at Karya Ibul julnior high school Palelmbang in 2019. Relselarch analytic was ulsing a cross selctional approach. Samplels ulseld as many 85 girls, sampling telchniqulels ulsing total sampling telchniqulels. Statistical telst of chi-sqularel with a significant of α = 0,05. Thel relsullts of thel stuldy of 85 stuldelnts, which bellongs to thel catelgory of thin BMI 27 stuldelnts elxpelrielnceld melnstrulal disordelr as many as 21 stuldelnts (77,8%), BMI catelgory of obelsity as many as 7 stuldelnts (85,7%), sulffelreld 6 felmalel melnstrulal disordelr (85,7%), thel normal BMI catelgory of 51 stuldelnts elxpelrielncing 19 melnstrulal disordelr (37,3%). Chi-sqularel statistical telst relsullts obtaineld a p-valulel = 0,001 valulel of lelss than α = 0,05 (p-valulel ≤ α). From thel stuldy, thelrel is a melaningfull significant of melnstrulal disordelr and thel (BMI) on girl stuldelnts at Karya Ibul julnior high school Palelmbang in 2019.